Utilizing Storytelling Technique Using Finger Puppet in Teaching Vocabulary Mastery to Young Learner - Ira Riyani (Universitas Suryakancana, 2019)
Vocabulary is one of the most important things to teach English to young learners, however in the practice it faced some issues especially on the use of medias, the use of media which is not interesting can make students’ easy to get bored in learning. This research paper is intended at increasing vocabulary mastery and describing the implementation of teaching vocabulary by using storytelling to teach vocabulary to the fifth grader students of Jamaras elementary school. This research focused to get insight on the implementation of storytelling by using finger puppet in teaching vocabulary to young learners, to find out the strength and weaknesses of teaching vocabulary through story telling using finger puppet, and to find out the students response in teaching vocabulary through storytelling using finger puppet. This study employed a qualitative design. The researcher used two narrative stories to gather the data. Concerning the qualitative data, this research collected and analyzed data from classroom observation, guided interview, and guided questionnaire. This research was conducted in elementary school in Cianjur, involving a teacher and students of Jamaras elementary school. The participants were ten students of the fifth grade. The findings show, that storytelling by using finger puppet is beneficial to teach vocabulary, because it made the student easy to get new vocabulary. Whereas the strengths of the use of storytelling using puppet in teaching vocabulary were the students were more interested and not bored in the learning process. The weaknesses of the use of implementation storytelling using puppet was the students more focus on puppet than on the story that conveyed by the teacher and also from the students response from the questionnaire teaching vocabulary through storytelling can help them to get the new vocabulary in a fun way.